Aspectos clínicos, laboratoriais e radiológicos de pacientes internados com suspeita de coqueluche - Tereza Rebecca de Melo e Lima; Paula Ferdinanda Conceição de Mascena Diniz Maia; Gabriela Barreto Almeida Vasconcelos; Maria Luísa Gomes Bezerra; Maria Beatriz Rodrigues Esteves Moura; Yane Ferreira Cardoso; Lucas Miranda Castro; Patrícia Clericuzi de Barros e Silva (Sociedade Brasileira de Pediatria, 2023)
OBJECTIVE: Describe the profile of patients admitted with signs of pertussis, emphasizing the differences between confirmed cases and its differential diagnosis. METHODS: Retrospective study realized by the analysis of medical charts of patients from 0 to 2 years old, admitted between 2015 to 2019 with suspected pertussis. Epidemiological, clinical, laboratorial, and radiological variables were verified. The data was analyzed descriptively and through associations. RESULTS: 211 patients were included, being 81,1% levss than 6 months old and 49,3% male. At the admission, high frequency of coughing (99.1%), paroxysmal coughing (60,2%), cyanosis (78,7%) and dyspnea (70,1%) was observed. Data showed that 8,4% of the patients who underwent leukogram presented lymphocytic leukocytosis, and 57,5% of the patients submitted to chest X-ray presented abnormalities. The pertussis diagnosis was confirmed in only 37 patients. There was significative association (p<0,005) between pertussis and the variables: cyanosis, post-cough vomiting, inspiratory squeak, tachypnea, respiratory auscultation abnormalities and leukocytosis. Furthermore, 72,9% of the patients did not get the vaccine or the schedule was incomplete. CONCLUSIONS: The presentation of pertussis, in general, is similar to other respiratory infections, being fundamental the maintenance of the epidemiological surveillance to collaborate with the diagnosis, reduce use of macrolides and adequate the prophylactic measures.